FOXG1 Transcriptionally Orchestrates Parvalbumin+ Interneuron Function Contributing to Schizophrenia Pathology - Pengfei Jiang; Mingzhao Su; Xue Zhou; Baoshen Zhang; Jie Sun; Ru Ba; Junhua Liu; Chunjie Zhao (Neuroscience Bulletin, 2026)
Schizophrenia (SCZ) is characterized by heterogeneous symptoms including abnormal perception, social withdrawal, and cognitive deficits. Parvalbumin-positive (PV + ) interneurons are particularly vulnerable in SCZ; however, the underlying cellular basis remains unclear. In this study, we found that selective deletion of the SCZ risk gene Foxg1 in PV + interneurons of mice recapitulated aspects of the disease phenotype, including impaired sensorimotor gating, anxiety-like behavior, social deficits, and cognitive impairments. Foxg1 deficiency caused dendritic simplification, reduced spine density, and impaired synaptic transmission in PV + interneurons of the prelimbic cortex. Our findings indicate that FOXG1 directly drives a set of SCZ risk genes that encode synaptic receptors, adhesion molecules, scaffolding proteins, transporters, ion channels, and vesicle-trafficking proteins, thereby orchestrating PV + interneuron synaptic function. Notably, FOXG1 activates the transcription of metabotropic glutamate receptor 3 (mGluR3), and pharmacological potentiation of mGluR3 activity alleviates behavioral deficits in Foxg1 conditional knockout mice. In conclusion, our findings identify a novel role for Foxg1 in PV + interneurons, providing new mechanistic insights into their vulnerability to SCZ.